EFFECTIVENESS OF CRITICAL READING STRATEGY TOWARD GUIDANCE AND COUNSELING STUDENTS’ CRITICAL THINKING SKILL - Ummah, Syifaul (Journal of Innovation Research and Knowledge, 2024)
This research was aimed at finding out the effectiveness of critical reading strategy for enhancing critical thinking of the of second semester guidance and counseling students of University of Nahdlatul Ulama Al Ghazali Cilacap in the academic year 2023/2024. This research used quantitative research with experimental design. The sample of the research was 29 students. The sample was selected by using purposive sampling technique. The data were analyzed by using pretest and post test. The mean score in pretest was 60 while the mean score of post test was 75. The mean score difference was 15. The result showed that is a difference in learning result before and after applying critical reading strategies. the N-gain score obtained was 0,43. Therefore, it can be concluded that critical reading strategy was quite effective for enhancing guidance and counseling students’ critical thinking.